2019
DOI: 10.1038/s41558-019-0460-6
|View full text |Cite
|
Sign up to set email alerts
|

The UK summer heatwave of 2018 and public concern over energy security

Abstract: The UK summer heatwave of 2018 led to changes in consumer behaviour, including large increases in electricity demand due to increased use and intensity of refrigeration and aircondition devices (1, 2). While the UK experienced its equal hottest summer on record, the extreme temperatures were concentrated in the south and east of England (3). We exploit the regional variation to test for the effect of experiencing extreme temperatures on resource security perceptions and related pro-environmental behaviour. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…That same meta-analysis found that perceived self-capacity had higher effects on adaptation behaviors than experience. Larcom (2019) found that experience with a heatwave amongst the general population did not elicit adaptation behaviors in the United Kingdom, but did elevate concern [ 41 ]. Similarly, Albright and Crow (2019) found that direct flooding experience was not a predictor of concern for climate change amongst Colorado, United States, residents [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…That same meta-analysis found that perceived self-capacity had higher effects on adaptation behaviors than experience. Larcom (2019) found that experience with a heatwave amongst the general population did not elicit adaptation behaviors in the United Kingdom, but did elevate concern [ 41 ]. Similarly, Albright and Crow (2019) found that direct flooding experience was not a predictor of concern for climate change amongst Colorado, United States, residents [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…A changing climate has led to increases in both mean and extreme temperatures globally since the 1950s, driven largely by anthropogenic greenhouse gas (GHG) emissions (IPCC, 2014). Research on heat waves (warm temperature extremes) is of central importance, because they exert disproportionate impacts on societies and ecosystems compared to mean climate (e.g., Larcom et al, 2019; Mora et al, 2017; Yuan et al, 2016). More intense, frequent, and longer‐lasting heat waves are projected in a future warmer climate (Meehl & Tebaldi, 2004; Russo et al, 2014), consistent with the trend of the past decades in observations (Alexander et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a recent meta-analysis performed by van Valkengoed and colleagues (2019) found that experience had small-to-moderate effects on climate change adaptation. Moreover, Larcom (2019) found that experience with a heatwave amongst the general population did not elicit adaptation behaviors in the United Kingdom, but did elevate concern [43]. Similarly, Albright and Crow (2019) found that direct flooding experience was not a predictor of concern for climate change amongst Colorado, United States, residents [44].…”
Section: Research On the Psychological Distance Of Climate Changementioning
confidence: 99%